2021
DOI: 10.1007/s00484-021-02127-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of desert dust storms, air pollution, and temperature on morbidity due to spontaneous abortions and toxemia of pregnancy: 5-year analysis

Abstract: Epidemiological studies have suggested an association between particulate air pollution, increased temperatures, and morbidity related to pregnancy outcomes. However, the roles of desert dust storms and climatological factors have not been fully addressed. The objectives of the present study were to investigate the association between desert dust storms, particulate matter with a diameter ≤10 μm (PM 10 ), daily temperatures, and toxemia of pregnancy and spontaneous abortion in Gaziantep, South East Turkey. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Several studies have reported that exposure to air pollution during pregnancy increases the risk of spontaneous abortion [5,49,50]. Gaskins et al reported that 1-year and 2-year exposures to PM2.5-10 prior to pregnancy were associated with a higher risk of spontaneous abortion [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that exposure to air pollution during pregnancy increases the risk of spontaneous abortion [5,49,50]. Gaskins et al reported that 1-year and 2-year exposures to PM2.5-10 prior to pregnancy were associated with a higher risk of spontaneous abortion [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the inhalation of pollutants dispersed in the atmosphere adversely affects human health (4)(5)(6)(7)(8)(9)(10). High level of car traffic, increased combustion of fossil fuels for industrial activities, transport, and domestic heating lead to elevated levels of air pollutants including particulate matter (PM) levels in the atmosphere (4).…”
Section: Introductionmentioning
confidence: 99%
“…High level of car traffic, increased combustion of fossil fuels for industrial activities, transport, and domestic heating lead to elevated levels of air pollutants including particulate matter (PM) levels in the atmosphere (4). Air pollution causes human health problems such as respiratory, cardiovascular, cerebrovascular, and obstetric diseases (4,5,(7)(8)(9)(10)(11). Basic biological mechanisms that explain the effects of air pollutants on vascular structures are still controversial (3).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that there is a direct link between exposure to high amounts of dust particles and the number of daily hospitalizations and deaths (Karanasiou et al 2012;Rublee et al, 2020;Herrera-Molina et al, 2021). Exposure to dust particles during dust events can cause respiratory and cardiovascular problems (Zhang et al, 2016;Toure et al, 2019;Rublee et al, 2020); increase the probability of low birth weight and premature birth (Dastoorpoor et al, 2018;Jones, 2020;Bogan et al, 2021); cause different diseases, such as meningitis (Diokhane et al, 2016) and valley fever (Middleton, 2020); and, in rare cases, end in death (Crooks et al, 2016;Zhang et al, 2016). Information on the increase in particle concentrations and the change in particle sizes with the degradation of air quality during dust events can help develop an understanding of the impact that these events have on people who are exposed to them.…”
Section: Introductionmentioning
confidence: 99%